Peningkatan Kompetensi Spiritual Care Perawat Menggunakan Metode Reflektif Praktis - Yulia Arianti; Luky Dwiantoro; Meidiana Dwidianti; Madya Sulisno (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The aim of this research is to find out practical reflective methods that are suitable for improving nurses' spiritual care competence. This research uses the scoping review method. Literature search on electronic databases namely SCOPUS, Science Direct, ProQuest. The time the article was published was January 2013 to December 2022. The final search results were 7 articles that met the inclusion criteria. There are three themes, namely group reflection methods that are appropriate to be applied in the clinical area of nursing, the role of the facilitator for reflection groups as the key to conveying the spiritual care experience of nurses, and a conducive teaching and learning environment in the clinical area. The conclusion from this research is that there is a need for reflection methods that are adapted to the needs of nurses in clinical areas. Nursing management can carry out guided group reflection methods for implementing nurses and training facilitators to lead group reflection. Apart from that, a safe and comfortable environment is needed in sharing experiences in groups. Keywords: Nurse Competency, Reflective Practice, Spiritual care